Heritability of sensory attributes in a diverse group of rye accessions - Elżbieta Szuleta; Timothy Phillips; Jarrad W. Gollihue; Seth DeBolt; Robert Perry; David A. Van Sanford (Applied Food Research, 2023)
Increasing interest in products made from rye grain underscores the need for developing improved rye (Secale cereale L.) cultivars. In the context of consumer appeal, there are specific questions about the sensory attributes of different rye cultivars. Unfortunately, there are very few studies that focus on the flavor and other sensory attributes of rye products. In order to estimate rye-derived aroma and flavor variability, we evaluated sensory attributes in rye flatbread of forty-seven rye entries, selected from commercial rye cultivars and international accessions that are adapted to our latitude. Additionally, we evaluated distillates from eleven rye cultivars and breeding lines. We found significant differences in flatbread aroma and flavor (P < 0.001) and significant overall distillate aroma differences (P < 0.05) among tested rye entries. In our flatbread screening, heritability of nutty (h2 = 0.37), salty (h2 = 0.57), grassy (h2 = 0.37), toasted (h2 = 0.55), and raw dough-like (h2 = 0.34) flavor notes, and sweet (h2 = 0.29), fermented (h2 = 0.34), musty (h2 = 0.33), grassy (h2 = 0.37) and toasted (h2 = 0.5) aroma notes were found significant; the number of distillates evaluated was too small to estimate this parameter. We developed rye distillate aroma and flavor prediction models based on sensory evaluation of easy and quick-to-prepare flatbread. This manuscript proposes the usage of flatbread to evaluate rye grain aroma and flavor for sensory research purposes and for flavor prediction of other rye products.